Youth Out of Touch? Early Assessment of Millennial Leaders’ Performance on Human Capital Development at Indonesian Districts - Nur Hidayat Sardini; Bangkit Aditya Wiryawan; Rina Martini (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
Starting in the second round of local election, participation of millenials has been increasing. The term refers to the young demographic cohort born between 1980 and 2002, known to have distinct characteristics to the previous generations. We gathered seventeen cases of elected millennial district heads between 2010 and 2017 and making an early observation of their impact on human capital development. Simplified difference-in-difference estimation method is applied using province average as the control group. Results show that following the winning of the millennial leaders there is a diverging trend of Human Development Index score at 0.03 and 0.07 in the first and second year, consecutively, before started converging around the third and fourth year. Lacking leadership skills and experiences, that may also be perpetrated by generational gap, are among the contributing factors to the problem. We further find that leaders not affiliated with political dynasty fare better. We check the robustness of our result using poverty data and further find that millennial leaders are also under-perform in combating poverty. This early assessment would benefit from further heterogeneity analyses as well as narrowing the control group, which is our recommendation for future research.